Kepemimpinan feminis yang memulihkan di masa duka: Suksesor gembala perempuan Gereja-gereja Pentakostal di Indonesia - Sumual, Ivonne Sandra (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2025)
This study explores the dynamics of female leadership succession in Indonesian Pentecostal churches, particularly when pastors' wives automatically inherit leadership roles after their husbands' deaths. Using a narrative qualitative approach framed by feminist hermeneutics and trauma theology, this study examines the experiences of female leaders who are survivors, employing the conceptual frameworks of Holy Saturday and Middle Spirit from Shelly Rambo, as well as the Table Principle and Community of Hospitality from Letty Russell. The findings show that the logic of structural inheritance often overlooks the spiritual-emotional healing needs of grieving leaders, thereby reproducing suffering rather than fostering healing. This study affirms that restorative feminist leadership requires the church to suspend the functionalistic logic of succession, provide space for hospitality, and uphold gender justice as fidelity to the work of the Holy Spirit in forming authentic and transformative leadership. Abstrak Penelitian ini mengeksplorasi dinamika suksesi kepemimpinan perempuan dalam Gereja-gereja Pentakostal Indonesia, khususnya ketika istri gembala secara otomatis mewarisi peran kepemimpinan pasca-kematian suaminya. Melalui pendekatan kualitatif naratif yang dibingkai her-meneutika feminis dan teologi trauma, penelitian ini membaca pengalaman para pemimpin perempuan penyintas dengan kerangka konseptual Holy Saturday dan Middle Spirit dari Shelly Rambo, serta Table Principle dan Community of Hospitality dari Letty Russell. Temuan menunjukkan bahwa logika pewarisan struktural kerap mengabaikan kebutuhan pemulihan spiritual-emosional pemimpin yang berduka, sehingga gereja justru menjadi aktor reproduksi penderitaan alih-alih komunitas penyembuh. Penelitian ini menegaskan bahwa kepemimpinan feminis yang memulihkan menuntut gereja menunda logika fungsionalistik suksesi, memberi ruang hospitalitas, dan menegakkan keadilan gender sebagai kesetiaan pada karya Roh Kudus dalam membentuk kepemimpinan yang otentik dan transformatif.